1979
DOI: 10.1016/s0378-4347(00)81638-2
|View full text |Cite
|
Sign up to set email alerts
|

Urinary excretion of methylated purines in man and in the rat after the administration of theophylline

Abstract: SUMMARYChromatographic characteristics of urinary metabolites of theophylline were studied by two-dimensional thin-layer chromatography, high-performance liquid chromatography and gas chromatography-mass spectrometry. Quantitative data for the urinary metabolites of theophylline in asthmatic children are given. It was shown that 1,3-dimethyluric acid is the predominant excretory product. In addition, smaller amounts of 1-methyluric acid, 3-methylxanthine and unchanged theophylline were found. Excretory pattern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1981
1981
2010
2010

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…4). Qualitative similarities between the rabbit and other species in the metabolism of 1,3-DMX were confirmed (7,10,(22)(23)(24)(25)(26)(27)(28), and suggested that the same enzyme system is involved in the 1,3-DMX metabolism in the species concerned. Quantitative comparisons with previous studies in rabbits are not possible because the only report up to now was in 1951 (29), when knowledge and analytical methods were less refined.…”
Section: Resultsmentioning
confidence: 78%
See 1 more Smart Citation
“…4). Qualitative similarities between the rabbit and other species in the metabolism of 1,3-DMX were confirmed (7,10,(22)(23)(24)(25)(26)(27)(28), and suggested that the same enzyme system is involved in the 1,3-DMX metabolism in the species concerned. Quantitative comparisons with previous studies in rabbits are not possible because the only report up to now was in 1951 (29), when knowledge and analytical methods were less refined.…”
Section: Resultsmentioning
confidence: 78%
“…Described here for the first time is the complete metabolic pattern of 1,3-DMX in the rabbit, which mainly metabolizes the compound to 1,3-DMV (66% of the administered dose, Fig. 4) as man, dog, mouse and rat do, although the amount of metabo- lite produced is two-three times higher than other species (7,10,(22)(23)(24)(25)(26)(27)(28). Thus, it appears that this species has only limited possibilities, compared to other species, of metabolizing 1,3·DMX, if the enzyme system responsible for oxidation of 1,3-DMX to 1,3-DMU becomes saturated (Figs.…”
Section: Resultsmentioning
confidence: 99%
“…Equilibrate the chromatographic column with Buffer A for 20 min at 1.2 mL/min and 10 • C prior to the injection of any standards or biological sample. (5), hypoxanthine (6), thymine (7), xanthine (8), ascorbic acid (9), uridine (10), adenine (11), SAM (14), inosine (15), uric acid (16) guanosine (17), thymidine (18) orotic acid (19), SAH (24), AICAR (25), adenosine (26), SAICAR (28), succinyladenosine (29), and adenylosuccinate (31) was performed at 260 nm. In Panel B, the assignment of peaks to propionic acid (12), GSH (13), malonic acid (20), methylmalonic acid (21), NAA (22), NAG (23), GSSG (27), and NAAG (30) was performed at 206 nm.…”
Section: Hplc Equipment and Chromatographic Run Conditionsmentioning
confidence: 99%
“…It is therefore evident that purine and pyrimidine profiling in biological fluids plays a critical role for both clinicians and IEM-affected patients (8)(9)(10). Based on the physical-chemical characteristics of those purines and pyrimidines with clinical-biochemical significance, various methods have been proposed during the last decade based on the use of high-performance liquid chromatography (HPLC) coupled with either UV-VIS (11)(12)(13)(14)(15)(16)(17)(18) or mass spectrometric (19)(20)(21)(22)(23) detectors, capillary electrophoresis (24,25), thin-layer chromatography (TLC) (26), and gas chromatography-mass spectrometry (GC-MS) (27).…”
mentioning
confidence: 99%